Peningkatan Motivasi pada Pembelajaran Akidah Akhlak melalui Media Audio Visual di MAS Muta’allimin Blang Bintang - Silahuddin Silahuddin (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The teacher is a learning component that plays an important and main role, because the success of the teaching and learning process is largely determined by the teacher factor. The teaching and learning process of teachers at MAS Muta'allimin Meulayo Blang Bintang generally still uses the lecture method and only uses blackboard media in teaching, so students get bored easily and some fall asleep. This study aims to determine student responses to the use of audio-visual media in Akidah Akhlak learning in class X MAS Muta'allimin Meulayo-Blang Bintang and to determine students' motivation to learn by using audio-visual media in learning Akidah Akhlak in class X MAS Muta'allimin Meulayo. -Blang Bintang. The method used in this research is classroom action research or commonly abbreviated as CAR. Classroom action research (CAR) is action research conducted with the aim of improving the quality of classroom learning practices. The results of the research on student responses to the use of audio-visual media in the first cycle with a percentage of 77, 88% included in the category of good criteria. While in the second cycle with a percentage of 82, 69% and belongs to the very good category. Student learning motivation in the first cycle with a percentage of 80.6% is in the good category, and in the second cycle has increased with a percentage of 98.8% and is classified into the very good category. The use of audio-visual media in Aqidah Morals lessons can increase students' learning motivation.